NHE1 expression at wound margins increases time‐dependently during physiological healing. Issue 2 (9th January 2017) - Haverkampf, Sonja; Heider, Judith; Weiß, Katharina T.; Berneburg, Mark; Karrer, Sigrid; Schreml, Stephan; Haubner, Frank; Ettl, Tobias; Schreml, Julia; Hedtrich, Sarah; von Süßkind‐Schwendi, Marietta; Dissemond, Joachim
Abstract: Wound repair is an orchestrated process, encompassing the phases of inflammation, proliferation and tissue remodeling. In this context, sodium hydrogen exchanger 1 (NHE1) is crucial to epidermal barrier integrity and acidification. Recently, we found that extracellular pH (pHe) on wound surfaces is dramatically increased initially after barrier disruption, and that pHe decreases gradually during physiological healing. Additionally, we have shown that spatial NHE1‐patterns account for pHe‐gradients on surfaces of chronic wounds. Here, we show that NHE1‐expression is very low at margins initially after wounding and that it increases massively during the time‐course of physiolgical healing. This finding is in accordance with the decrease of pHe on wound surfaces, which we reported on in previous works. Thus, we show that NHE1 is an interesting target when it comes to modification of surface pHe on wounds, both acute and chronic, and that NHE1 is time‐dependently regulated in physiological healing.